PENERAPAN METODE NAÃVE BAYES PADA KASUS GANGGUAN PSIKOLOGIS PADA MASA PANDEMI COVID-19 - Annisa Alfu (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2023)
The COVID-19 pandemic is a type of deadly virus that has become a new cause of stress. Physical and psychological health is the hope of every individual. But not all individuals can enjoy this health because of contracting a disease. Stress experienced by individuals can affect physiological functions, namely there are 4 diseases in psychological disorders including stress, depression, anxiety disorders and social phobia. Therefore we need a web-based system using the nave Bayes method by paying attention to the symptoms experienced which will help psychological disorders in recognizing mental health against Covid-19 transmission during the pandemic. In this study, the data in question is psychological data due to the COVID-19 pandemic. There are many modern algorithms created to diagnose symptoms due to this pandemic, but here the researcher wants to prove that NaÃ¯ve Bayes can also perform the diagnosis quite well. Nave Bayes has a high accuracy value so that it can be used for various purposes, including for document classification, spam detection and other classification problems. The use of the NaÃ¯ve Bayes method in this study can be rated as a material for research evaluation. With the Naive Bayes method in the rating, it can be seen from the disease. The results of this study are a desktop program for the diagnosis of stress, depression, anxiety disorders, and social phobias during the covid-19 pandemic.